Enhancing the oxidation resistance of nanocrystalline high-entropy AlCuCrFeMn alloys by the addition of tungsten - Dewangan, Sheetal Kumar; Kumar, Devesh; Sharma, Ashutosh; Ahn, Byungmin; Kumar, Vinod (Journal of Materials Research and Technology, 2022)
The isothermal oxidation behavior of multi-component high entropy alloys (HEAs), namely AlCuCrFeMn, AlCuCrFeMnW0.05, AlCuCrFeMnW0.1, and AlCuCrFeMnW0.5, was investigated and the behavior of the oxide layer was analyzed. All four HEAs were synthesized via mechanical alloying (MA) and consolidated by spark plasma sintering (SPS). The samples were oxidized in the air atmosphere at a temperature of 500 °C for 50 h. Based on the thermogravimetric result, the oxidation rate of the materials decreased with the increase of W content, and the values of parabolic constants were on a level similar to those observed in Ni-Al superalloys. However, higher content of W improves the continuity and internal position of the WO3 scale, which leads to increased oxidation resistance. Throughout the oxidation process, the composition of the phases of all materials changed significantly. The triple-thick oxide layer formed of Al2O3, Cr2O3, and WO3, developed in HEAs, has been carefully studied using the XPS technique.
Keywords: Air atmosphere; High entropy alloys; Isothermal oxidations; Multicomponents; Nanocrystallines; Oxidation behaviours; Oxide layer; Oxide resistance; Spark-plasma-sintering; Synthesised; High-entropy alloy; Nanocrystalline; Oxide resistance; Powder metallurgy